2014
DOI: 10.1016/j.febslet.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Aim24 stabilizes respiratory chain supercomplexes and is required for efficient respiration

Abstract: a b s t r a c tThe mitochondrial respiratory chain is essential for the conversion of energy derived from the oxidation of metabolites into the membrane potential, which drives the synthesis of ATP. The electron transporting complexes bc 1 complex and the cytochrome c oxidase assemble into large supercomplexes, allowing efficient energy transduction. Currently, we have only limited information about what determines the structure of the supercomplex. Here, we characterize Aim24 in baker's yeast as a protein, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Aim24 localizes to the mitochondrial IM and is required for the integrity of the MICOS complex. Studies with yeast Aim24 deletion mutants revealed that this gene is required for respiratory growth, stability of ETC supercomplexes and mitochondrial ultrastructure [64,65]. Whereas mitochondria from cells lacking Aim24 do not manifest an altered cardiolipin composition, when Aim24 deletion is combined with subtle modifications (appending a His-Tag sequence) to other MICOS proteins (MIC12 or MIC26), an altered cardiolipin acyl chain pattern is observed, with a shift toward longer, more saturated acyl chains.…”
Section: Protein Modulators Of Crista Membrane Structure and Cardmentioning
confidence: 99%
“…Aim24 localizes to the mitochondrial IM and is required for the integrity of the MICOS complex. Studies with yeast Aim24 deletion mutants revealed that this gene is required for respiratory growth, stability of ETC supercomplexes and mitochondrial ultrastructure [64,65]. Whereas mitochondria from cells lacking Aim24 do not manifest an altered cardiolipin composition, when Aim24 deletion is combined with subtle modifications (appending a His-Tag sequence) to other MICOS proteins (MIC12 or MIC26), an altered cardiolipin acyl chain pattern is observed, with a shift toward longer, more saturated acyl chains.…”
Section: Protein Modulators Of Crista Membrane Structure and Cardmentioning
confidence: 99%
“…MICOS has also been implicated in cardiolipin biogenesis and maturation. Destabilization of MICOS in cells lacking Aim24, a Mic10 interactor of unknown function, causes alterations in cristae architecture and loss of tafazzin, leading to a non‐native cardiolipin acylation pattern . Tafazzin is a transacylase that exchanges cardiolipin acyl groups depending on membrane curvature and resulting tension in the bilayer, thereby generating the species‐specific acyl composition of cardiolipin that is best suited thermodynamically for the respective inner membrane architecture .…”
Section: Nonbilayer‐forming Phospholipidsmentioning
confidence: 99%
“…PRwf-1, P. glacincola BNF20 would belong to group I, which contains a gene encoding a protein exhibiting the AIM24 domain, also found in the P. glacincola BNF20 TIGR00266 protein. Although no role has been ascribed to it in prokaryotes, in higher organisms it is an internal membrane protein related to mitochondrial biogenesis which is required for yeast respiration (Deckers et al, 2014). The AIM24 domain exhibits a double beta-helix folding, which is frequently found in genes neighboring TerD, suggesting that both proteins could interact (Anantharaman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%